Peran Lingkungan Sekolah dalam Membentuk Identitas Keislaman Anak Usia Dini di KB Cahaya Asri Sei Dadap Asahan - Erni, Erni; Rahman, Mhd Habibu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the role of the school environment in shaping the Islamic identity of early childhood children at Cahaya Asri Kindergarten in Sei Dadap, Asahan. Islamic identity is an important part of early childhood character formation, which includes the introduction of basic Islamic values such as monotheism, morals, worship, and social behavior. This study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation with teachers, principals, parents, and students. The results showed that a conducive and Islamic-nuanced school environment plays a significant role in shaping children's Islamic identity. Habitual religious activities such as reciting prayers, memorizing short surahs, practicing ablution and prayer, as well as teachers' role models in behaving in an Islamic manner have a positive influence on children's religious behavior. In addition, parental involvement in school activities also strengthens the process of internalizing Islamic values at home. A consistently supportive and Islamic school environment can be an effective medium for instilling Islamic identity in early childhood. Collaboration between schools, teachers, and parents is the key to success in shaping children's religious character from an early age.